Immunological and inflammatory biomarkers of susceptibility and severity in adult respiratory syncytial virus infections - Wiseman,DJ; Thwaites,RS; Drysdale,SB; Janet,S; Donaldson,GC; Wedzicha,JA; Openshaw,PJ; RESCEU,Investigators (Journal of Infectious Diseases, 2020)
BACKGROUND: . Respiratory syncytial virus (RSV) is the most common cause of bronchiolitis in young infants. However, it is also a significant pathogen in older adults. Validated biomarkers of RSV disease severity would benefit diagnostics, treatment decisions, and prophylactic interventions. This review summarizes knowledge of biomarkers for RSV disease in adults. METHODS: A literature review was performed using Ovid Medline, Embase, Global health, Scopus, and Web of Science for articles published 1946-October 2016. Nine articles were identified plus 9 from other sources. RESULTS: From observational studies of natural infection and challenge studies in volunteers, biomarkers of RSV susceptibility or disease severity in adults were: (1) lower anti-RSV neutralizing antibodies, where neutralizing antibody (and local IgA) may be a correlate of susceptibility/severity; (2) RSV-specific CD8+ T cells in bronchoalveolar lavage fluid preinfection (subjects with higher levels had less severe illness); and (3) elevated interleukin-6 (IL-6), IL-8, and myeloperoxidase levels in the airway are indicative of severe infection. CONCLUSIONS: Factors determining susceptibility to and severity of RSV disease in adults have not been well defined. Respiratory mucosal antibodies and CD8+T cells appear to contribute to preventing infection and modulation of disease severity. Studies of RSV pathogenesis in at-risk populations are needed.